Dyslipidemia and associated factors among adult type two diabetes mellitus patients in Felege Hiywot Refral, Hospital, Bahir Dar, Ethiopia, 2023 - Addis, Zemenu; Nega, Ayenew Tega; Tebeje, Robel Demelash; Asmare, Engdaw; Tegegnie, Alemu Bezabih; Tamir, Workineh; Alene, Tamiru (Frontiers in Cardiovascular Medicine, 2024)
BackgroundDyslipidemia is a common condition in type two diabetic patients, and it is thought to have a significant role in moderating the cardiovascular risk associated with diabetes. Data on serum lipid profiles in type 2 diabetes patients from Bahir Dar, Ethiopia is limited. This study aimed to evaluate the prevalence of dyslipidemia among adult type 2 diabetes patients and to explore potential contributing factors.Method and materialsA facility-based cross-sectional study was conducted with 354 type 2 diabetes mellitus patients from April 3 to June 4, 2023. Data were collected through the use of structured questionnaires and checklists. The data were entered into EpiData version 4.6 and analyzed using SPSS version 26. Logistic regression was employed to identify variables significantly associated with the outcomes, with a p-value ≤ 0.05 and a 95% confidence interval.ResultsA total of 369 individuals with diabetes were approached in this study, resulting in a response rate of 96%. The overall prevalence of dyslipidemia was 61.3% (95% CI: 56.2–66.7). Of those with dyslipidemia, 11% had a single serum lipid abnormality, while 50.3% had a combined serum lipid abnormality. Significant factors associated with dyslipidemia included being over 60 years old (AOR: 2.4, 95% CI: 1.2–5.0), poor fasting blood glucose control (AOR: 2.5, 95% CI: 1.2–5.1), being overweight (AOR: 5.8, 95% CI: 3.2–11), physical inactivity (AOR: 3.4, 95% CI: 1.7–7.0), and being a past alcohol drinker (AOR: 3.1, 95% CI: 1.3–7.4).ConclusionIn the study area, a high prevalence of dyslipidemia was found among diabetic patients. Independent factors associated with dyslipidemia included older age, poor fasting blood glucose control, physical inactivity, a history of alcohol consumption, and being overweight. To address this issue, it is essential to implement preventive measures such as early detection, patient education, dietary monitoring, regular clinical visits, physical exercise, and weight management. These strategies represent the most effective approach to combating dyslipidemia.